Electric Control of 2D Van Hove Singularity in Oxide Ultra‐Thin Films. Issue 17 (20th March 2023) - Kim, Donghan; Kim, Younsik; Sohn, Byungmin; Kim, Minsoo; Kim, Bongju; Noh, Tae Won; Kim, Changyoung
Abstract: Divergent density of states (DOS) can induce extraordinary phenomena such as significant enhancement of superconductivity and unexpected phase transitions. Moreover, van Hove singularities (VHSs) lead to divergent DOS in 2D systems. Despite recent interest in VHSs, only a few controllable cases have been reported to date. In this work, by utilizing an atomically ultra‐thin SrRuO3 film, the electronic structure of a 2D VHS is investigated with angle‐resolved photoemission spectroscopy and transport properties are controlled. By applying electric fields with alkali metal deposition and ionic‐liquid gating methods, the 2D VHS and the sign of the charge carrier are precisely controlled. Use of a tunable 2D VHS in an atomically flat oxide film could serve as a new strategy to realize infinite DOS near the Fermi level, thereby allowing efficient tuning of electric properties. Abstract : A van Hove singularity (VHS) possesses an infinite density of states at a certain energy point when it exists in two dimensions. By taking advantage of this two‐dimensional VHS property, it is demonstrated that the type of charge carrier can be tuned in oxide ultrathin film systems, showing the potential for practical devices.